2007
DOI: 10.1093/treephys/27.4.561
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime transpiration in woody plants from contrasting ecosystems

Abstract: It is commonly assumed that transpiration does not occur at night because leaf stomata are closed in the dark. We tested this assumption across a diversity of ecosystems and woody plant species by various methods to explore the circumstances when this assumption is false. Our primary goals were: (1) to evaluate the nature and magnitude of nighttime transpiration, E(n), or stomatal conductance, g(n); and (2) to seek potential generalizations about where and when it occurs. Sap-flow, porometry and stable isotope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
331
6
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(382 citation statements)
references
References 63 publications
33
331
6
1
Order By: Relevance
“…Some studies have reported that the response of different species to rainfall pulses and plant water use strategies would be various within a given area (Noy-Meir, 1973;Reynolds et al, 2004). For example, shrub species in the Proteaceae, such as Isopogon gardneri rapidly increased their sap flow (by up to 5 times) after 34 mm of rainfall event in southern Australia, whereas deep-rooted eucalyptus species were sufficiently reliant on antecedent soil condition that they did not respond to precipitation (Amenu and Kumar, 2008;Dawson et al, 2007). These results agreed with those reported by Xu and Li (2006) based on studies of the photosynthesis of Haloxylon ammodendron and Tamarix ramosissima.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that the response of different species to rainfall pulses and plant water use strategies would be various within a given area (Noy-Meir, 1973;Reynolds et al, 2004). For example, shrub species in the Proteaceae, such as Isopogon gardneri rapidly increased their sap flow (by up to 5 times) after 34 mm of rainfall event in southern Australia, whereas deep-rooted eucalyptus species were sufficiently reliant on antecedent soil condition that they did not respond to precipitation (Amenu and Kumar, 2008;Dawson et al, 2007). These results agreed with those reported by Xu and Li (2006) based on studies of the photosynthesis of Haloxylon ammodendron and Tamarix ramosissima.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have exploited environmental variation to show g night can be affected by environmental factors. For example, water stress (as soil drought, salinity, and high atmospheric demand) reduces g night and E night in many species (Rawson and Clarke 1988;Donovan et al 1999;Barbour and Buckley 2007;Cavender-Bares et al 2007;Dawson et al 2007;Fisher et al 2007;Howard and Donovan 2007;Moore et al 2008). Although each of these studies has illuminated several aspects of g night by focusing on either genetic or environmental effects, how these factors interact to influence g night has not been directly addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Although each of these studies has illuminated several aspects of g night by focusing on either genetic or environmental effects, how these factors interact to influence g night has not been directly addressed. Such interactions may confound current interpretations of variation in natural populations (Caird et al 2007a;Dawson et al 2007;Scholz et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Beside, if the weather is cloudy and less sunlight, volume of water also decrease in time. Transpiration process plant will be higher in the presence of abundant sunshine compared with less sunlight conditions [15].…”
Section: Water Samplingmentioning
confidence: 99%